Karakteristik Vaginal Birth After Caesarean (VBAC) pada Ibu dengan Locus Minoris Resistentiae (LMR) Periode Januari 2017 - Desember 2020 - Putu Ayu Bunga Aurellia; Pande Made Ngurah Geriawan; Ni Wayan Armerinayanti (Aesculapius Medical Journal, 2023)
Vaginal Birth After Cesarean (VBAC) is a normal delivery process after having previously had a cesarean section. This process is carried out on mothers with former cesarean sections or Locus Minoris Resistant (LMR). The aim of this study was to find out the characteristics of Vaginal Birth After Caesarean (VBAC) in Mothers with Locus Minoris Resistance (LMR) for the period January 2017-December 2020. This study was a retrospective descriptive study with a sample of mothers with LMR who performed VBAC at the Sanjiwani Hospital. Gianyar, BRSUD Tabanan and RS Prima Medika Denpasar which were selected by purposive sampling method that met the inclusion criteria were then presented in tabular form. There were 37 patients out of 48 patients who underwent Trial of Labor After Caesarean (TOLAC) who successfully performed a VBAC with various characteristics, where as many as 32 people (86.5%) with age < 35 years, did not have a history of normal delivery as many as 24 people ( 64.9%), having a cesarean section frequency 1 time as many as 36 people (97.3%), patients with an indication of a previous cesarean section in a breech presentation as many as 14 people (37.9%), with a delivery distance of > 24 months as many as 37 people ( 100%) and gave birth to babies with a birth weight of 2500-4000 grams as many as 36 people (97.3%).